NATIONAL PROJECT «LABOR PRODUCTIVITY AND SUPPORT OF EMPLOYMENT» IN THE SYSTEM OF SUSTAINABLE ECONOMIC DEVELOPMENT - S. Poluektova (Вестник Северо-Кавказского федерального университета)
The article analyzes the low level of labor productivity in the country, identifies a number ofproblems that constrain the growth of labor productivity, as well as the directions of its increase. It is established that the increase in labor productivity is the most important factor that ensures the growth of the national and regional economy. One of the priorities in this area for coming years (2019-2024) should be the implementation of a national project of labor productivity growth. The key objective of this project is to stimulate interest on the part of regional and federal authorities, enterprises and to ensure the growth of labor productivity in enterprises of basic non-resource industries. The national project will include measures to encourage enterprises to increase productivity, reduce administrative and legal restrictions, create a system of management training, etc. An important link in this project is the development and implementation of labor productivity programs in the regions of the Russian Federation and enterprises of the regions.